Factors associated with diagnostic delay and prognosis in hospitalized patients with strongyloidiasis in Okinawa, Japan. - Seishiro Arima; Naoya Nishiyama; Yuri Higure; Yui Naha; Teruhito Uchihara; Shuhei Ideguchi; Hideta Nakamura; Kazuya Miyagi; Masashi Nakamatsu; Shusaku Haranaga; Takeshi Kinjo; Akihiro Tokushige; et al. (PLoS Neglected Tropical Diseases)
Background Prognosis and factors correlated to diagnostic delays in patients with strongyloidiasis, a parasitic disease, remain poorly understood. This study investigated the relationship among diagnostic delay, prognosis, and eosinophilia in patients with strongyloidiasis. Methodology/principal findings Hospitalized patients with a confirmed diagnosis of strongyloidiasis at a single hospital over 10 years (2013-2023) were retrospectively screened. Fifty-five inpatients were included (median age, 81 years); 34 patients (61.8%) were male, and all but one patient was born in Okinawa before 1960. Duration from onset of symptoms to diagnosis was 10 days (median), hospitalization length was 37 days (median), and eight patients (14.5%) died. We classified diagnoses made after ≥30 days as delayed diagnosis and compared the patients with and without delayed diagnosis. Patients with delayed diagnosis had more in-hospital deaths than their counterparts (55.6% versus [vs.] 7.1%, P < 0.005). Compared with patients diagnosed earlier, those with delayed diagnosis were also characterized by older age (90 vs. 78.5 years, P < 0.005), more frequent fever (55.6% vs. 19.6%, P = 0.037), lower hemoglobin levels (10.1 vs. 11.8 g/dL, P = 0.0363), absence of eosinophilia (0% vs. 22%, P = 0.015), higher rates of sepsis (50% vs. 10.7%, P = 0.03), and prolonged hospitalization (77 vs. 23.5 days, P < 0.005). Diagnostic delay even after adjusting for age and sex using multivariate logistic regression analyses was a significant risk factor for mortality (odds ratio = 11.3, P = 0.022). Patients without eosinophilia were older than those with eosinophilia (84.5 vs. 76 years, P = 0.005) and not associated with in-hospital death (23.3% vs. 4.8%, P = 0.118). Conclusions/significance Diagnostic delays are associated with a poor prognosis of strongyloidiasis. The absence of eosinophilia led to overlooked diagnoses. Screening should be considered before starting immunosuppressive therapy; relying on eosinophil counts could delay diagnosis.